2013
DOI: 10.1080/09585192.2012.712545
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management in Asian subsidiaries: comparison of French and Japanese MNCs

Abstract: European and Japanese multinational corporations (MNCs) have expanded their activities in Asia, usually through massive mobilization of various human resources from head offices, whether expatriated or on short-term assignments, and a reliance on diverse categories of local employees. Because expatriation is costly, difficult and often limited in its results, MNCs have developed localization strategies for management positions to support their regional development. This contribution addresses such a scenario b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 32 publications
0
13
0
3
Order By: Relevance
“…In this respect, some changes from an ethnocentric toward a polycentric and sometimes even geocentric staffing policy have emerged in recent years. For example, Schaaper et al (2013) compared French and Japanese MNCs operating in eight Asian countries and found that although Japanese MNCs localize management positions less than French MNCs, they are reducing the number of expatriates sent to subsidiaries in Asia. Moreover, they found that Japanese MNCs send experts to subsidiaries on short-term assignments as frequently as French MNCs, suggesting that Japanese MNCs are using short-term assignments to reduce expatriation and promote localization.…”
Section: Localization Among Japanese Mncsmentioning
confidence: 98%
“…In this respect, some changes from an ethnocentric toward a polycentric and sometimes even geocentric staffing policy have emerged in recent years. For example, Schaaper et al (2013) compared French and Japanese MNCs operating in eight Asian countries and found that although Japanese MNCs localize management positions less than French MNCs, they are reducing the number of expatriates sent to subsidiaries in Asia. Moreover, they found that Japanese MNCs send experts to subsidiaries on short-term assignments as frequently as French MNCs, suggesting that Japanese MNCs are using short-term assignments to reduce expatriation and promote localization.…”
Section: Localization Among Japanese Mncsmentioning
confidence: 98%
“…Le recours aux expatriés facilite l'intégration globale des filiales alors que l'utilisation des cadres locaux est favorable à la réactivité locale (Schaaper et al, 2012). A chaque entreprise d'établir l'équilibre entre ces deux types de ressources managériales en fonction du contexte où elle se situe.…”
Section: Revue De La Littératureunclassified
“…En conséquence, les entreprises s'efforcent de limiter le nombre d'expatriés en localisant autant que faire se peut les postes de management, c'est-à-dire en les confiant à des cadres locaux (Harzing, 2001;Fayol-Song, 2011). Cela requiert toutefois le développement d'une politique complète de GRH des personnels locaux, en termes de formation (la quatrième dimension de contrôle considérée ici), d'évaluation, de promotion, et de fidélisation de ces personnels, comme l'ont étudié Schaaper et al (2012) en contexte asiatique.…”
Section: L'adaptation Des Mécanismes De Coordination Et De Contrôleunclassified
“…Les expatriés, en effet, sont exposés aux spécificités de l'environnement local, et s'efforceront d'y répondre en référence aux valeurs, pratiques, solutions et exigences de la maison mère diffusées mondialement, et en fonction de ses intérêts globaux. En outre, en appui des expatriés et pour en limiter le nombre, les entreprises ont développé massivement les missions de courte durée d'experts et techniciens à l'international, le recrutement local de ressortissants du pays ou la zone d'origine de l'entreprise multinationale, et autres formules intermédiaires n'impliquant plus le déménagement de la famille du cadre (Mayerhofer et al, 2004;Schaaper et al, 2012).…”
Section: L'adaptation Des Mécanismes De Coordination Et De Contrôleunclassified